Pengaruh Ozonisasi terhadap Kekerasan, Kadar Air, Vitamin C, dan Total Mikroorganisme pada Belimbing (Averrhoa carambola) Selama Penyimpanan - Imas Siti Setiasih; Tita Rialita; Debby Moody Sumanti; In In Hanidah; Gemma Zulhaida (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Starfruit is a non-climacteric fruit which are perishable after harvesting and during storage. One of compounds that can be used to maintain starfruit quality is the use of ozone water. This study was conducted to compare the characteristics of starfruit without ozonation and after ozonation using TIP-01 ozonizer during storage time in the room temperature (25±2ºC). The method used was the experimental method and then analyzed using a correlations-regressions analysis. The study used 2 treatments which were starfruit without ozonation and with ozonation (immersion in ozon water), the star fruits were packed by using a cling wrap with Styrofoam as the base. The results showed that starfruits from both treatments had changes in water content, vitamin C, and firmness (decreased). Ozone treatment with a concentration of 1.1 ppm was only able to inhibit the growth of microorganisms by 0.34 log CFU/g. Starfruits’ intact ozonation results in higher vitamin C content at 31.9680 mg/100g of material at the end of storage.